Potentiometric and Spectroscopic Studies on Nickel(II) 1,4,7,10-tetraazacyclododecane Complexation and Thermodynamic Aspects - MUTLU, HASENE; AYDIN, RAHMIYE; OZER, ULVIYE (Asian Journal of Chemistry, 2010)
The complex formation equilibria of nickel(II) with 1,4,7,10-tetraazacydododecane (cyclam, L) were investigated in 0.1 mol L-1 ionic strength medium, by KCl at three different temperatures (25°, 35° and 45°C). In this research, potentiometric and spectroscopic titrations were applied that were not performed before in cited studies. The protonation constants of H2L2+ and HL+ type ions of cyclen were defined; they were in good agreement with other works. The formation constant of NiH2L4+ type complex was determined and thus its occurrence in lower pH range was proved that had not taken place in other Ni(II)-cyclam studies. In higher pH range the existence of NiL2+ type complex was identified and its formation constant was defined. It was noticed that the stabilities of either NiH2L4+ and NiL2+ complexes decrease with temperature. By means of speciation diagram the existences of NiH2L4+ and NiL2+ complexes were also verified. The overall changes in thermodynamic parameters (ΔH, ΔS and ΔG) associated with NiL2+ complex formation equilibrium were evaluated graphically.